2013
DOI: 10.1016/j.cpc.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Multi-frequency based location search algorithm of small electromagnetic inhomogeneities embedded in two-layered medium

Abstract: In this paper, we consider a problem for finding the locations of electromagnetic inhomogeneities completely embedded in homogeneous two layered medium. For this purpose, we present a filter function operated at several frequencies and design an algorithm for finding the locations of such inhomogeneities. It is based on the fact that the collected Multi-Static Response (MSR) matrix can be modeled via a rigorous asymptotic expansion formula of the scattering amplitude due to the presence of such inhomogeneities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Kirchhoff and subspace migration imaging techniques operated at single and multiple time-harmonic frequency has been applied successfully not only for full-but also limitedview inverse scattering problem if the number of directions of incident field and corresponding scattered field are sufficiently large enough. Related works can be found in [7,24,26,32,39,41,42,46,49] and reference therein. Although these techniques are very robust with respect to the random noise and media, and offer very good results for imaging of small and extended scatterers, it is still used in many research field without rigorous mathematical theory.…”
Section: Introductionmentioning
confidence: 99%
“…Kirchhoff and subspace migration imaging techniques operated at single and multiple time-harmonic frequency has been applied successfully not only for full-but also limitedview inverse scattering problem if the number of directions of incident field and corresponding scattered field are sufficiently large enough. Related works can be found in [7,24,26,32,39,41,42,46,49] and reference therein. Although these techniques are very robust with respect to the random noise and media, and offer very good results for imaging of small and extended scatterers, it is still used in many research field without rigorous mathematical theory.…”
Section: Introductionmentioning
confidence: 99%
“…Based on explored structures, we confirmed that the shapes of small anomalies can be retrieved by imaging function without diagonal elements of the scattering matrix, and this is a considerable improvement over the traditional technique. Following several works [39,43,53,59], it has been shown that subspace migration is effective in a limitedaperture inverse scattering problem. The application and development of a microwave imaging technique to the limited-aperture problem is an interesting problem.…”
Section: Resultsmentioning
confidence: 99%
“…Our current research considers cracks with Dirichlet boundary conditions; we plan to extend our research to cracks with Neumann boundary conditions (soundhard arc in inverse acoustic scattering problem), refer to [11,12]. Furthermore, motivated by [2,7,10,18,20], extending our research to the limited-view inverse scattering problem will be an interesting research topic. …”
Section: Results Of Numerical Simulations and Finding Exact Locationsmentioning
confidence: 99%